Migrant nurses in Brazil: demographic characteristics, migration flow and relationship with the training process - Kênia Lara Silva; Roseni Rosângela de Sena; Tatiana Silva Tavares; Stephanie Marques Moura Franco Belga; Lucas Wan Der Maas (Universidade de São Paulo, 2016)
Objective to analyze the migration of nurses in Brazil, describe the demographic characteristics of migrant nurses, the main migration flows, and establish relationships with the training process. Method a descriptive, exploratory study, based on 2010 Census data. The data were analyzed using descriptive statistics. Result there were 355,383 nurses in Brazil in 2010. Of these, 36,479 (10.3%) reported having moved compared to the year 2005: 18,073 (5.1%) for intrastate migration, 17,525 (4.8%) interstate migration, and 871 (0.2%) international migration. Females (86.3%), Caucasians (65.2%), and unmarried (48.3%) nurses prevailed in the population, without considerable variation between groups according to migration situation. The findings indicate that the migration flows are driven by the training process for states that concentrate a greater number of courses and positions in undergraduate and graduate studies, and the motivation of employment opportunity in regions of economic expansion in the country. Conclusion it is necessary to deepen the discussion on the movement of nurses in Brazil, their motivations, and international migration.